Interactive Literature: Shifting Reading Patterns in the Era of Apps and Digital Platforms - Beata Sitinjak, Shenny Ayunuri (PT. Anagata Sembagi Education, 2025)
The rapid rise of digital technologies and mobile applications has significantly reshaped how people interact with literature, shifting reading from static print to interactive, multimodal experiences. This study investigates how interactive literature in apps and digital platforms alters reading patterns, comprehension, participation, and aesthetic experience. Using a systematic literature review (SLR), articles published between 2019 and 2025 were collected from major databases, screened through a PRISMA protocol, and synthesized using thematic analysis. A total of 48 eligible studies were reviewed to capture global perspectives on interactive reading practices. The findings reveal three main themes. First, interactive navigation through branching narratives, hyperlinks, and multimedia shifts reading from linear to non-linear, promoting agency but sometimes overwhelming readers. Second, interactivity enhances engagement, motivation, and vocabulary recall while enriching aesthetic immersion; however, its effects on deep comprehension remain inconsistent. Third, demographic and digital literacy factors moderate outcomes, with younger and digitally experienced readers navigating interactivity more effectively, while cultural and socioeconomic contexts shape participation styles. The study concludes that interactive literature expands rather than replaces traditional reading, offering opportunities for participatory and creative engagement while raising challenges for sustaining critical comprehension. These insights provide a foundation for future educational applications and design of digital reading platforms.